Toward Novel Antioxidant Drugs: Quantitative Structure-Activity Relationship Study of Eugenol Derivatives - Priyagung Dhemi Widiakongko; Karisma Triatmaja (Walisongo Journal of Chemistry, 2021)
The study of the Quantitative Structure-Activity Relationship (QSAR) of eugenol compound and its derivatives towards antioxidant activities was conducted using electronic and molecular descriptors. These descriptors were generated from semi-empirical chemical computation with PM3 level of theory. The QSAR model in this research could be used to predict novel antioxidant compounds which are more potent. The activity of the compound determined based on the IC50 value (Inhibition Concentration 50%) was linked with the descriptor results that had been calculated in a QSAR equation. The data showed that the descriptors that had a significant effect were a net charge of C-6, C-7, O-12, and HOMO energy and hydration energy. The best QSAR equations obtained with these descriptors and their parameters are shown as follows.log1/IC50 = - 3,3026 (± 0,4066) qC6 - 4,7450 (± 0,7224) qC7 + 3,2746 (± 0,6752) qO12 + 0,6326 (± 0,0645) HOMO - 0,0086 (± 0,0011) hydration energy + 4,8053 (± 0,6336)(n = 8 ; R = 1,000 ; s = 0,004 ; F = 3655,537 ; p = 0,0003 ; Q2 = 0,988 ; SPress = 0,039 ; SDEP = 0,021)